Bifunctional bamboo-like CoSe2 arrays for high-performance asymmetric supercapacitor and electrocatalytic oxygen evolution. (19th March 2018) - Chen, Tian; Li, Songzhan; Gui, Pengbin; Wen, Jian; Fu, Xuemei; Fang, Guojia
Abstract: Bifunctional bamboo-like CoSe2 arrays are synthesized by thermal annealing of Co(CO3 )0.5 OH grown on carbon cloth in Se atmosphere. The CoSe2 arrays obtained have excellent electrical conductivity, larger electrochemical active surface areas, and can directly serve as a binder-free electrode for supercapacitors and the oxygen evolution reaction (OER). When tested as a supercapacitor electrode, the CoSe2 delivers a higher specific capacitance (544.6 F g −1 at current density of 1 mA cm −2 ) compared with CoO (308.2 F g −1 ) or Co3 O4 (201.4 F g −1 ). In addition, the CoSe2 electrode possesses excellent cycling stability. An asymmetric supercapacitor (ASC) is also assembled based on bamboo-like CoSe2 as a positive electrode and active carbon as a negative electrode in a 3.0 M KOH aqueous electrolyte. Owing to the unique stucture and good electrochemical performance of bamboo-like CoSe2, the as-assembled ACS can achieve a maximum operating voltage window of 1.7 V, a high energy density of 20.2 Wh kg −1 at a power density of 144.1 W kg −1, and an outstanding cyclic stability. As the catalyst for the OER, the CoSe2 exhibits a lower potential of 1.55 V (versus RHE) at current density of 10 mA cm −2, a smaller Tafel slope of 62.5 mV dec −1 and an also outstanding stability.